A homogenization heat treatment method for Zr-containing aluminum-lithium alloy
Through the two-stage homogenization treatment method, the first-stage treatment that gradually reduces the heating rate and the second-stage treatment that rapidly heat-raising and insulation solve the problem of difficulty in achieving diffuse phase precipitation and second-phase redissolution in the prior art, and realizes the problem of the difficulty of simultaneously realizing diffuse phase precipitation and second-phase redissolution in the prior art. The efficient uniformization of aluminum-lithium alloys improves performance and process efficiency.
Patent Information
- Application Number
- CN202211365576.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-31
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-10-31
AI Technical Summary
The existing homogenization heat treatment technology of aluminum-lithium alloys is difficult to achieve uniform precipitation of the diffuse phase and good redissolution of the Ag-containing and Cu-rich phases simultaneously. The third-level homogenization treatment time is too long and is not suitable for industrial applications.
The two-stage homogenization treatment method is adopted. The first stage treatment includes three heating sections, which gradually reduces the heating rate to ensure the uniform nucleation of the diffuse phase and the redissolution of the Ag-containing phase; the second stage treatment is rapid heating and long-term insulation. Achieve rapid redissolution of Cu-rich phases.
It achieves uniform precipitation of the diffuse phase and good redissolution of the Ag-containing and Cu-rich phases, improves the structural uniformity and performance of aluminum-lithium alloys, shortens the process operation time, and is suitable for industrial applications.
Smart Images

Figure CN116497296B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum-lithium alloy production, and in particular to a homogenization heat treatment method for Zr-containing aluminum-lithium alloy. Background Art
[0002] Aluminum-lithium alloy has the properties of light weight, high strength, high elastic modulus, etc., and is widely used in the aerospace field. Generally speaking, there will be obvious dendrite segregation in the cast structure of aluminum-lithium alloy, and there will be coarse Cu-rich phase and Ag-containing phase adjacent to the Cu-rich phase at the grain boundary in the cast structure. The dissolution temperature of the Ag-containing phase is about 495-505℃, and the dissolution temperature of the Cu-rich phase is 510-520℃. The primary process of alloy deformation processing is to dissolve the coarse second phase through appropriate homogenization treatment. In addition, during the homogenization process, except for the dissolution of the equilibrium eutectic phase, the trace element Zr in the alloy can form an Al3Zr dispersed phase with a size of tens of nanometers and coherent with the matrix, which can pin the grain boundary and inhibit recrystallization in the subsequent hot deformation process, effectively improving the performance of the aluminum-lithium alloy product.
[0003] The patent with publication number CN 112831736 A discloses a two-stage homogenization annealing process for 2099 aluminum-lithium alloy, which can effectively eliminate the residual crystalline phase in the alloy ingot and make the ingot obtain the ideal uniformity of structure and composition. However, this technical solution only considers the dissolution of Ag-containing phase and Cu-rich phase, and does not involve the precipitation of dispersed phase.
[0004] Patent publication number CN 114561578 A discloses a two-stage homogenization heat treatment process for high Cu / Li ratio alloys, which takes into account the heating rates of the first and second stages, but is only intended to dissolve back the second phase with a high Cu content and is not suitable for aluminum-lithium alloys with other compositions.
[0005] The patent with publication number CN 108456836 A discloses a method for preparing aluminum-lithium alloy, and determines that the optimal homogenization process is 410℃ / 4h+490℃ / 24h, which achieves the homogenization of the composition and the grain size of about 200μm. Although this technical solution takes into account the precipitation control of the dispersed phase, the dissolution of the Cu-rich phase under the homogenization treatment of 490℃ / 24h is general, and the homogenization effect cannot be guaranteed.
[0006] Combining the methods of patents CN 112831736A and CN 108456836 A, if a three-stage homogenization treatment system is used to respectively ensure the precipitation of dispersed phase, the dissolution of Ag-containing phase, and the dissolution of Cu-rich phase, the process operation time is too long, which is not conducive to industrial application. Summary of the invention
[0007] In view of the shortcomings of the above-mentioned prior art, the present invention provides a homogenization heat treatment method for a Zr-containing aluminum-lithium alloy, which can achieve uniform precipitation of a dispersed phase and good dissolution of an Ag-containing phase and a Cu-rich phase.
[0008] The present invention is achieved through the following technical solutions.
[0009] A homogenization heat treatment method for a Zr-containing aluminum-lithium alloy, comprising: a first-stage homogenization treatment, a second-stage homogenization treatment;
[0010] The first stage homogenization treatment includes: a first heating stage, a second heating stage, and a third heating stage; the first heating stage is to heat the Zr-containing aluminum-lithium alloy from room temperature to 435-445°C, and the heating rate is gradually reduced from 250-350°C / h to 5-10°C / h during the heating process, and the heating time is 2-3h; the second heating stage is to heat the Zr-containing aluminum-lithium alloy from 435-445°C to 445-455°C, and the heating rate is gradually reduced from 5-10°C / h to 2-5°C / h during the heating process, and the heating time is 1-3h; the third heating stage is to heat the Zr-containing aluminum-lithium alloy from 445-455°C to 455-465°C at a heating rate of 2-5°C / h, and the heating time is 2-4h, and then keep warm; the overall time of the first stage homogenization treatment is 5-10h, and the insulation time is 15-30h;
[0011] The second-stage homogenization treatment is to heat the Zr-containing aluminum-lithium alloy that has undergone the first-stage homogenization treatment to 515-520° C. for 1-3 hours and then keep the temperature for 18-40 hours.
[0012] Furthermore, the first-stage homogenization treatment takes a total of 6 to 9 hours, and the heat preservation time is 16 to 28 hours.
[0013] Furthermore, the preferred holding time during the second stage homogenization treatment is 20 to 38 hours.
[0014] Furthermore, the Zr content in the Zr-containing aluminum-lithium alloy is 0.09-0.20 wt.%.
[0015] Beneficial technical effects of the present invention:
[0016] a) By controlling the heating rate during the first stage homogenization heating process, uniform nucleation of the dispersed phase is achieved during the first to third heating stages; during the first stage homogenization temperature insulation process, the dispersed phase grows uniformly, and the Ag-containing phase basically dissolves back into the matrix, leaving only the Cu-rich phase as the remaining dissolvable second phase.
[0017] b) The second stage homogenization is quickly heated to a higher temperature and then kept warm, which effectively realizes the rapid dissolution of the Cu-rich phase.
[0018] c) The homogenization treatment method of the present invention realizes uniform precipitation of the dispersed phase, good dissolution of the Ag-containing phase and the Cu-rich phase, so that the ingot obtains an ideal structure and improves the efficiency of the homogenization heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a schematic process diagram of a highly efficient homogenization heat treatment method for a Zr-containing aluminum-lithium alloy.
[0020] Figure 2 The present invention discloses a scanning structure of a Zr-containing aluminum-lithium alloy in the as-cast state.
[0021] Figure 3 This is a cast DSC curve of a Zr-containing aluminum-lithium alloy of the present invention.
[0022] Figure 4 This is the scanned tissue after the first level of homogenization processing of the present invention.
[0023] Figure 5 This is the DSC curve after the first stage homogenization treatment of the present invention.
[0024] Figure 6 This is the transmission morphology of the dispersed phase particles after the first stage homogenization treatment of the present invention.
[0025] Figure 7 This is the scanned tissue after the second level homogenization treatment of the present invention.
[0026] Figure 8 This is the DSC curve after the second stage homogenization treatment of the present invention. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] After research, it was found that the dissolution temperature of the Ag-containing phase is about 495-505°C, but it has a relatively fast dissolution rate below this temperature, which may overlap with the precipitation temperature range of the Al3Zr dispersed phase, achieving the effect of simultaneous dissolution of the Ag-containing phase and precipitation of the dispersed phase in a relatively low temperature range.
[0029] The process flow of the aluminum-lithium alloy high-efficiency homogenization heat treatment method of the present invention is as follows: Figure 1 As shown in the figure, it mainly includes: (1) the first stage homogenization treatment, in which the heating process is a process of gradually decreasing heating rate, the insulation temperature is high and the temperature window is narrow, which realizes the dissolution of the Ag-containing phase while realizing the uniform precipitation and growth of the dispersed phase. (2) The second stage homogenization treatment realizes the rapid dissolution of the Cu-rich phase in a higher temperature window.
[0030] Specifically, a homogenization heat treatment method for a Zr-containing aluminum-lithium alloy, a homogenization heat treatment method for a Zr-containing aluminum-lithium alloy, comprising: a first-stage homogenization treatment, a second-stage homogenization treatment;
[0031] The first stage homogenization treatment includes: a first heating stage, a second heating stage, and a third heating stage; the first heating stage is to heat the Zr-containing aluminum-lithium alloy from room temperature to 435-445°C, and the heating rate is gradually reduced from 250-350°C / h to 5-10°C / h during the heating process, and the heating time is 2-3h; the second heating stage is to heat the Zr-containing aluminum-lithium alloy from 435-445°C to 445-455°C, and the heating rate is gradually reduced from 250-350°C / h to 5-10°C / h during the heating process. The temperature is gradually reduced from 5 to 10 ° C / h to 2 to 5 ° C / h, and the heating time is 1 to 3 hours; the third heating stage is to heat the Zr-containing aluminum-lithium alloy from 445 to 455 ° C to 455 to 465 ° C at a heating rate of 2 to 5 ° C / h, and the heating time is 2 to 4 hours, and then keep warm; the first-level homogenization treatment takes a total of 5 to 10 hours, and the insulation time is 15 to 30 hours; preferably, the total time is 6 to 9 hours, and the insulation time is 16 to 28 hours;
[0032] The second stage homogenization treatment is to heat the Zr-containing aluminum-lithium alloy that has undergone the first stage homogenization treatment to 515-520° C. for 1-3 hours and then keep the temperature for 18-40 hours, and the preferred holding time is 20-38 hours.
[0033] Furthermore, the Zr content in the Zr-containing aluminum-lithium alloy is 0.09-0.20 wt.%.
[0034] Example 1
[0035] 2195 aluminum-lithium alloy (Al-3.8Cu-0.5Mg-1.2Li-0.45Ag-0.2Mn-0.2Zn-0.11Zr, wt.%), ingot specification is Φ135mm.
[0036] like Figure 2 , which is the as-cast scanning structure of the alloy of Example 1. It can be seen from the figure that the coarse non-equilibrium eutectic phase in the as-cast structure is the Ag-containing phase and the Cu-rich phase.
[0037] like Figure 3 As shown, it is the DSC curve of the cast alloy of Example 1. It can be seen from the figure that there are two endothermic peaks in the cast structure, corresponding to the Ag-containing phase and the Cu-rich phase, and their initial melting temperatures are 505.8°C and 513.9°C, respectively.
[0038] The alloy is homogenized by the method of the present invention, and the specific process is as follows: the first stage of homogenization starts from room temperature at a heating rate of 300°C / h, and the heating rate is gradually reduced; when the alloy temperature reaches 440°C, the heating rate is reduced to 10°C / h, and the time is 3h; when the alloy temperature reaches 450°C, the heating rate is reduced to 5°C / h, and the time is 1.5h; when the alloy is heated to 460°C at a heating rate of 5°C / h, it is kept warm, and the total heating time of the first stage of homogenization is 6.5h, and the heat preservation time is 24h. The second stage of homogenization has a heating time of 2h, and when the temperature reaches 515°C, it is kept warm for 30h.
[0039] like Figure 4 As shown, it is the scanning structure of the alloy of Example 1 after the first stage homogenization treatment. It can be seen from the figure that the network structure of the eutectic phase in the cast alloy has been disconnected, the Ag-containing phase has been basically dissolved back, and the Cu-rich phase is found to remain.
[0040] like Figure 5 As shown, it is the DSC curve of the alloy of Example 1 after the first stage homogenization treatment. It can be seen from the figure that there is only the endothermic peak of the Cu-rich phase in the alloy, and the initial melting temperature is 517.6°C.
[0041] like Figure 6 As shown, it is the transmission morphology of the dispersed phase particles of the alloy of Example 1 after the first stage homogenization treatment. It can be seen from the figure that Al3Zr dispersed phase with small size and uniform distribution is precipitated in the alloy.
[0042] like Figure 7 As shown, it is the scanning structure of the alloy of Example 1 after the second stage homogenization treatment. It can be seen from the figure that only the Fe-containing phase remains in the alloy.
[0043] like Figure 8 , which is the DSC curve of the alloy of Example 1 after the second stage homogenization treatment. It can be seen from the figure that the endothermic peak of the Cu-rich phase has disappeared.
[0044] Example 2
[0045] 2195 aluminum-lithium alloy (Al-4.1Cu-0.5Mg-1.1Li-0.3Ag-0.25Mn-0.2Zn-0.10Zr, wt.%), ingot specification is Φ135mm.
[0046] The alloy is homogenized by the method of the present invention, and the specific process is as follows: the first stage homogenization starts from room temperature at a heating rate of 320°C / h, and the heating rate is gradually reduced; when the alloy temperature reaches 442°C, the heating rate is reduced to 7°C / h, and the time is 2h; when the alloy temperature reaches 448°C, the heating rate is reduced to 5°C / h, and the time is 1h; when the alloy is heated to 460°C at a heating rate of 3°C / h, it is kept warm, and the total heating time of the first stage homogenization is 7h, and the heat preservation time is 23h. The second stage homogenization heating time is 2h, and the temperature is kept warm for 30h when it reaches 517°C.
[0047] Example 3
[0048] 2195 aluminum-lithium alloy (Al-4.3Cu-0.8Mg-0.8Li-0.4Ag-0.2Mn-0.2Zn-0.12Zr, wt.%), ingot specification is Φ135mm.
[0049] The alloy was homogenized by the method of the present invention, and the specific process was as follows: the first stage of homogenization was started from room temperature at a heating rate of 350°C / h, and the heating rate was gradually reduced; when the alloy temperature reached 445°C, the heating rate was reduced to 9°C / h, and the time was 2h; when the alloy temperature reached 455°C, the heating rate was reduced to 4°C / h, and the time was 2h; when the alloy was heated to 462°C at a heating rate of 2°C / h, it was kept warm, and the total heating time of the first stage of homogenization was 7.5h, and the holding time was 24h. The second stage of homogenization was 2.5h, and the temperature was kept warm for 37h when the temperature reached 520°C.
[0050] Example 4
[0051] 2195 aluminum-lithium alloy (Al-3.7Cu-0.4Mg-0.9Li-0.3Ag-0.2Mn-0.2Zn-0.10Zr, wt.%), ingot specification is Φ135mm.
[0052] The alloy was homogenized by the method of the present invention, and the specific process was as follows: the first stage of homogenization was started from room temperature at a heating rate of 300°C / h, and the heating rate was gradually reduced; when the alloy temperature reached 440°C, the heating rate was reduced to 8°C / h, and the time was 2h; when the alloy temperature reached 446°C, the heating rate was reduced to 5°C / h, and the time was 1h; when the alloy was heated to 460°C at a heating rate of 4°C / h, it was kept warm, and the total heating time of the first stage of homogenization was 6.5h, and the holding time was 23h. The second stage of homogenization was 1.5h, and the temperature was kept warm for 22h when the temperature reached 515°C.
[0053] Example 5
[0054] 2195 aluminum-lithium alloy (Al-3.7Cu-0.25Mg-0.8Li-0.25Ag-0.10Mn-0.2Zn-0.11Zr, wt.%), ingot specification is Φ135mm.
[0055] The alloy is homogenized by the method of the present invention, and the specific process is as follows: the first stage of homogenization starts from room temperature at a heating rate of 250°C / h, and the heating rate is gradually reduced; when the alloy temperature reaches 440°C, the heating rate is reduced to 10°C / h, and the time is 2h; when the alloy temperature reaches 445°C, the heating rate is reduced to 5°C / h, and the time is 1h; when the alloy is heated to 455°C at a heating rate of 5°C / h, it is kept warm, and the total heating time of the first stage of homogenization is 5h, and the holding time is 16h. The second stage of homogenization has a heating time of 1h, and when the temperature reaches 515°C, it is kept warm for 20h.
[0056] Example 6
[0057] 2099 aluminum-lithium alloy (Al-3.0Cu-0.2Mg-1.8Li-0.1Mn-0.4Zn-0.11Zr, wt.%), ingot specification is Φ135mm.
[0058] The alloy is homogenized by the method of the present invention, and the specific process is as follows: the first stage homogenization starts from room temperature at a heating rate of 300°C / h, and the heating rate is gradually reduced; when the alloy temperature reaches 435°C, the heating rate is reduced to 8°C / h, and the time is 2h; when the alloy temperature reaches 450°C, the heating rate is reduced to 5°C / h, and the time is 2h; when the alloy is heated to 460°C at a heating rate of 4°C / h, it is kept warm, and the total heating time of the first stage homogenization is 6.5h, and the heat preservation time is 20h. The second stage homogenization heating time is 1h, and the temperature is kept warm for 26h when it reaches 515°C.
[0059] Example 7
[0060] 2065 aluminum-lithium alloy (Al-4.7Cu-0.4Mg-1.4Li-0.25Ag-0.3Zn-0.2Mn-0.12Zr, wt.%), ingot specification is Φ135mm.
[0061] The alloy was homogenized by the method of the present invention, and the specific process was as follows: the first stage of homogenization was started from room temperature at a heating rate of 330°C / h, and the heating rate was gradually reduced; when the alloy temperature reached 442°C, the heating rate was reduced to 6°C / h, and the time was 2h; when the alloy temperature reached 455°C, the heating rate was reduced to 3°C / h, and the time was 3h; when the alloy was heated to 464°C at a heating rate of 3°C / h, it was kept warm, and the total heating time of the first stage of homogenization was 8h, and the holding time was 21.5h. The second stage of homogenization was 2.5h, and the temperature was kept warm for 36h when the temperature reached 520°C.
[0062] Example 8
[0063] 2050 aluminum-lithium alloy (Al-3.8Cu-0.6Mg-1.0Li-0.5Ag-0.3Mn-0.2Zn-0.12Zr, wt.%), ingot specification is Φ135mm.
[0064] The alloy was homogenized by the method of the present invention, and the specific process was as follows: the first stage of homogenization started from room temperature at a heating rate of 300°C / h, and the heating rate was gradually reduced; when the alloy temperature reached 443°C, the heating rate was reduced to 8°C / h, and the time was 2h; when the alloy temperature reached 450°C, the heating rate was reduced to 5°C / h, and the time was 1.5h; when the alloy was heated to 464°C at a heating rate of 4°C / h, it was kept warm, and the total heating time of the first stage of homogenization was 7h, and the holding time was 25h. The second stage of homogenization was 2h, and the temperature was kept warm for 27h when the temperature reached 515°C.
[0065] Comparative Example 1
[0066] The ingot used in Example 1 was used for homogenization treatment, and the specific process was as follows: the first stage homogenization heating time was 1.5 hours, and the temperature was kept at 500°C for 24 hours; the second stage homogenization heating time was 2 hours, and the temperature was kept at 515°C for 36 hours.
[0067] Comparative Example 2
[0068] The ingot used in Example 1 was used for homogenization treatment, and the specific process was as follows: the first stage homogenization was heating from room temperature at a heating rate of 10°C / min and keeping at 470°C for 20h; the second stage homogenization was heating at a heating rate of 4°C / min and keeping at 500°C for 36h.
[0069] Comparative Example 3
[0070] The ingot used in Example 1 was used for homogenization treatment, and the specific process was as follows: the first stage was heated for 4 hours and kept at 410°C for 12 hours; the second stage was heated for 2 hours and kept at 500°C for 36 hours.
[0071] Comparative Example 4
[0072] The ingot used in Example 1 was used for homogenization treatment, and the specific process was as follows: the first stage was heated for 4 hours and kept at 420°C for 12 hours; the second stage was heated for 5 hours and kept at 500°C for 28 hours; the third stage was heated for 3 hours and kept at 515°C for 30 hours.
[0073] The alloys after heat treatment according to the methods of Examples 1-11 and Comparative Examples 1-4 were analyzed. The results are shown in Tables 1 and 2.
[0074] Table 1 Dissolution effect of Ag-containing phase and Cu-rich phase under different homogenization heat treatment processes in the examples and comparative examples
[0075]
[0076]
[0077] Table 2 Precipitation results of dispersed phase under different homogenization heat treatment processes in the embodiments and comparative examples
[0078] Homogenization heat treatment solution <![CDATA[Number density (number / 100μm 2 )]]> Example 1 1135 Example 2 1109 Example 3 1258 Example 4 1251 Example 5 1043 Example 6 1065 Example 7 1105 Example 8 1209 Comparative Example 1 334 Comparative Example 2 98 Comparative Example 3 898 Comparative Example 4 916
[0079] It can be seen from Table 1 that, under the condition of ensuring good dissolution of the Ag-containing phase and the Cu-rich phase, the homogenization heat treatment method of the present invention takes a short overall time and has a high process efficiency. It can be seen from Table 2 that, under the condition of ensuring uniform precipitation of the dispersed phase, the number density of the dispersed phase obtained by the homogenization heat treatment method of the present invention is higher, and the precipitation result of the dispersed phase is better.
[0080] The homogenization heat treatment method of the present invention can effectively achieve good dissolution of the Ag-containing phase and the Cu-rich phase, and at the same time can ensure that the number density of the precipitated dispersed phase is higher and the precipitation effect is better. The method has strong operability and high heat treatment efficiency and can be applied under industrial conditions.
[0081] The above is only a preferred embodiment of the present invention and does not limit the invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, other equivalent improvements can be made, all of which can achieve the purpose of the present invention and should be regarded as the protection scope of the present invention.
Claims
1. A homogenization heat treatment method for a Zr-containing aluminum-lithium alloy, characterized in that: The method comprises: a first-stage homogenization process, a second-stage homogenization process; The first stage homogenization treatment includes: a first heating stage, a second heating stage, and a third heating stage; the first heating stage is to heat the Zr-containing aluminum-lithium alloy from room temperature to 435-445°C, and the heating rate is gradually reduced from 250-350°C / h to 5-10°C / h during the heating process, and the heating time is 2-3h; the second heating stage is to heat the Zr-containing aluminum-lithium alloy from 435-445°C to 445-455°C, and the heating rate is gradually reduced from 5-10°C / h to 2-5°C / h during the heating process, and the heating time is 1-3h; the third heating stage is to heat the Zr-containing aluminum-lithium alloy from 445-455°C to 455-465°C at a heating rate of 2-5°C / h, and the heating time is 2-4h, and then keep warm; the overall time of the first stage homogenization treatment is 5-10h, and the insulation time is 15-30h; The second-stage homogenization treatment is to heat the Zr-containing aluminum-lithium alloy that has undergone the first-stage homogenization treatment to 515-520° C. for 1-3 hours and then keep the temperature for 18-40 hours.
2. The homogenization heat treatment method of a Zr-containing aluminum-lithium alloy according to claim 1, characterized in that: The first stage homogenization treatment takes 6 to 9 hours in total, and the heat preservation time is 16 to 28 hours.
3. The homogenization heat treatment method of a Zr-containing aluminum-lithium alloy according to claim 1, characterized in that: The heat preservation time during the second stage homogenization treatment is 20 to 38 hours.
4. The homogenization heat treatment method of a Zr-containing aluminum-lithium alloy according to claim 1, characterized in that: The Zr content in the Zr-containing aluminum-lithium alloy is 0.09-0.20 wt.%.
Citation Information
Patent Citations
Aluminum-lithium alloy and preparation method thereof
CN108456836A
Two-stage homogenizing annealing process for aluminum-lithium alloy
CN112831736A
Aluminum-lithium alloy and heat treatment process thereof
CN114561578A
Heat treatment method of magnesium-containing cast aluminum lithium alloy
CN107190219A
Ultrahigh-strength aluminum-lithium alloy and preparation method thereof
CN110423927A